Ecological Status and Peoples’ Perception of Mistletoes in Panchase Protected Forest, Central Nepal Himalayas - Bohora, Dipak; Devkota, Mohan P. (Journal of Institute of Science and Technology, 2020)
Realizing the importance of Panchase Protected Forest, an important corridor of the Chitwan-Annapurna Landscape (CHAL) area, the ecological status and peoples’ perception of mistletoe was studied to supplement the information on mistletoes of Nepal Himalayas. Mistletoes were studied along the forest trails and data were collected within 10 m radius plots 20 m inside the trails to record the incidence of mistletoe occurrence and severity of infection during three field visits in 1917 and 1918. Fifty people were interviewed using a semi-structured questionnaire and Biodiversity Conservation Confidence Index was calculated to understand peoples' perceptions about mistletoes. A total of seven mistletoe species, six belonging to four genera in the family Loranthaceae, and a single genus in the family Viscaceae were documented from 27 host species belonging to 24 genera in 18 unrelated angiosperm host families. Loranthaceae mistletoes were more generalists having a wide host range while Viscaceae mistletoe showed a high degree of host specificity. The irregular and patchy distribution of mistletoe is governed by host availability, forest structure, and site mesoclimate. Knowledge regarding the importance and uses of mistletoes and its values in natural plant communities is limited to older generation people. Age groups, profession, and the mechanism of indigenous knowledge inheritance in the rural mountainous communities of the Panchase area are very poor and are eroding rapidly which is against promoting the indigenous knowledge system especially in the younger generation. More conservation initiatives are needed through the stakeholder involvement to protect the rich biodiversity of the area.